Linear Fractional Diferential Equations Systems: Sistemas Lineales de Ecuaciones Diferenciales Fraccionarias - González Nava, Erika (2025)
This paper focuses on the qualitative and quantitative description of solutions for linear systems of differential equations with fractional order. The Laplace transform and the Mittag-Leffler function are the main tools used to find such solutions. As in the ordinary case, the eigenvalues determine the stability of the system via a condition depending on the order of the fractional derivative. Finally, a fundamental theorem for linear fractional systems is proved, and some particular examples are given.